Distributed Global Debris Thickness Estimates Reveal Debris Significantly Impacts Glacier Mass Balance - Rounce, D. R.; Hock, R.; McNabb, R. W.; Millan, R.; Sommer, Christian; Braun, Matthias; Malz, Philipp; Maussion, F.; Mouginot, J.; Seehaus, Thorsten; Shean, D. E. (Geophysical Research Letters, 2021)
Supraglacial debris affects glacier mass balance as a thin layer enhances surface melting, while a thick layer reduces it. While many glaciers are debris-covered, global glacier models do not account for debris because its thickness is unknown. We provide the first globally distributed debris thickness estimates using a novel approach combining sub-debris melt and surface temperature inversion methods. Results are evaluated against observations from 22 glaciers. We find the median global debris thickness is ∼0.15 ± 0.06 m. In all regions, the net effect of accounting for debris is a reduction in sub-debris melt, on average, by 37%, which can impact regional mass balance by up to 0.40 m water equivalent (w.e.) yr-1. We also find recent observations of similar thinning rates over debris-covered and clean ice glacier tongues is primarily due to differences in ice dynamics. Our results demonstrate the importance of accounting for debris in glacier modeling efforts.
CRIS-Team Scopus Importer:2021-05-14
Keywords: debris thickness; glacier melt; glaciers; mass balance